2023
DOI: 10.1101/2023.07.24.550385
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Primary human lung fibroblasts exhibit trigger- but not disease-specific cellular senescence and impair alveolar epithelial cell progenitor function

Nora Bramey,
Maria Camila Melo-Narvaez,
Fenja See
et al.

Abstract: Aging is the main risk factor for chronic lung diseases including idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD). Accordingly, hallmarks of aging such as cellular senescence are increased in different cell types such as fibroblasts in the lungs of these patients. However, whether the senescent phenotype of fibroblasts derived from IPF or COPD differs is still unknown. Therefore, we characterized senescence at baseline and after exposure to disease-relevant insults (H2O2, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…(31) In mice models, p16-positive senescent murine lung fibroblasts promote epithelial stem cell regeneration after injury, (32) while a recent study demonstrated that senescence-induced human lung fibroblasts impaired murine alveolar epithelial cell progenitor function. (33) These studies suggest that there might be a tight balance, where transient senescence is supportive for tissue repair and persistent senescence is detrimental for tissue repair. (34) This balance may be tissue and (micro-) environment-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…(31) In mice models, p16-positive senescent murine lung fibroblasts promote epithelial stem cell regeneration after injury, (32) while a recent study demonstrated that senescence-induced human lung fibroblasts impaired murine alveolar epithelial cell progenitor function. (33) These studies suggest that there might be a tight balance, where transient senescence is supportive for tissue repair and persistent senescence is detrimental for tissue repair. (34) This balance may be tissue and (micro-) environment-dependent.…”
Section: Discussionmentioning
confidence: 99%